Comparative characterization of single cell activity in the globus pallidus internus of patients with dystonia or Tourette syndrome - Alam, Mesbah; Blahak, Christian (Journal of neural transmission, 2014)
Altered processing in the basal ganglia has been described both in dystonia and Tourette’s syndrome (TS). Deep brain stimulation (DBS) of the globus pallidus internus (GPi) has become a recognized treatment for dystonia and has been used successfully to alleviate tics in TS. This study evaluates possible differences of GPi linear and nonlinear neuronal discharge characteristics between patients with dystonia and TS. Nine patients with primary dystonia and six patients with TS were studied during functional stereotactic neurosurgical operations for implantation of DBS electrodes under general anesthesia. Six patients with primary dystonia under local anesthesia served as non-anesthetized controls. Single-unit activity recordings in the GPi were obtained during routine microelectrode recording and mapping to delineate nuclear borders and to identify the sensorimotor subregions. Anesthesia profoundly decreased neuronal activity in patients with dystonia. Dystonia patients showed marginally higher mean firing rates in the GPi compared to TS patients (P = 0.06). Although the average total number of bursts and the mean peak frequency in bursts did not differ between groups, the mean spikes in bursts were higher in dystonia patients (P < 0.05). Nonlinear time series analysis metrics, measured as complexity of Lempel-Ziv and maximum approximate entropy, revealed higher randomness in TS compared to dystonia patients (P < 0.05). The percentage of oscillating neurons in spike trains was higher in dystonia compared to TS (P < 0.05). Our data provide evidence for differences of the neuronal dynamic complexity, randomness and oscillatory modulation of spike trains in the GPi between dystonia and TS. Such differences, although subtle, might contribute to the specific clinical phenomenology secondary to disordered neuronal basal ganglia processing.
Gesehen am 29.11.2017